High-Voltage Electrostatic Fields Adversely Affect the Performance of Diamondback Moths over Five Consecutive Generations - Li Jia; Shicai Xu; Huanzhang Shang; Jiao Guo; Xia Yan; Changhai Liu; Guangwei Li; Kun Luo (Agronomy, 2023)
Changing electrical environments can influence the performance of herbivorous insects and adversely affect their control strategies. The diamondback moth, Plutella xylostella (L.), is a pest that devastates cruciferous vegetables. An age–stage, two-sex life table of P. xylostella over multiple generations was established to describe the effect of varying high-voltage electrostatic field (HVEF) exposure on their performance after the age-cohort eggs were exposed to HVEF at an intensity of 5.0 kV/cm for different durations. The results show that direct HVEF exposure adversely affected the population dynamics parameters of P. xylostella over multiple generations. In particular, the net reproduction rate, intrinsic natural increase rate, and finite increase rate of the P. xylostella population significantly decreased in the third and fifth generations under HVEF exposure for 10 min, while the mean generation time and doubling time significantly increased. Similarly, HVEF exposure for 10 min rapidly reduced the survival rate of adult P. xylostella in the first generation, and subsequently, it declined evenly and slowly. Meanwhile, the fecundity parameters of P. xylostella revealed that HVEF exposure for 10 min had the strongest inhibition effect on reproduction over five consecutive generations. In addition, HVEF exposure significantly increased the superoxide dismutase activity to produce extra hydrogen peroxide; however, increased catalase and peroxidase activity or reduced peroxidase activity triggered the accumulation of malondialdehyde in instar P. xylostella, especially after 10 min of treatment. The present findings provide experimental evidence and a theoretical basis for developing control strategies for P. xylostella under new HVEF environments.